2014
DOI: 10.1073/pnas.1321752111
|View full text |Cite
|
Sign up to set email alerts
|

Slow slip and the transition from fast to slow fronts in the rupture of frictional interfaces

Abstract: The failure of the population of microjunctions forming the frictional interface between two solids is central to fields ranging from biomechanics to seismology. This failure is mediated by the propagation along the interface of various types of rupture fronts, covering a wide range of velocities. Among them are the so-called slow fronts, which are recently discovered fronts much slower than the materials' sound speeds. Despite intense modeling activity, the mechanisms underlying slow fronts remain elusive. He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(87 citation statements)
references
References 39 publications
7
79
0
1
Order By: Relevance
“…Intermittent rupture then continues as long as the slow slip endures. A similar mechanism was found to control the transition from fast to slow rupture in a multi-asperity model [26], reproducing observations in laboratory experiments [4]. We also speculate that the start-stop regime found in this study may be an analog to observed periodic pulsing of aseismic events have been observed [16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Intermittent rupture then continues as long as the slow slip endures. A similar mechanism was found to control the transition from fast to slow rupture in a multi-asperity model [26], reproducing observations in laboratory experiments [4]. We also speculate that the start-stop regime found in this study may be an analog to observed periodic pulsing of aseismic events have been observed [16].…”
Section: Discussionsupporting
confidence: 90%
“…The range of observed front types have already been successfully reproduced by a variety of models. Arrested cracks have been reproduced using quasi-static models [18][19][20][21], or elastodynamic models in 1D [22,23] or 2D [24][25][26][27][28], assuming either continuous [19,[22][23][24][25]27] or discrete-microcontact-based friction laws [26,28], or fracture concepts [18,21]. Slip pulses have been reproduced using discrete [29] or continuum models assuming either a Coulomb [30], regularized Coulomb [31][32][33] or state-andrate [34,35] friction laws.…”
Section: Introductionmentioning
confidence: 99%
“…The different measures, from top to bottom, are defined in Eqs. (47)(48)(49). Note that (D.2) is identical to Fig.…”
Section: F Required Statisticsmentioning
confidence: 78%
“…Such improved models may incorporate those tangential interactions in ways similar to models already developed for the normal interactions during normal loading of rough surfaces (see e.g. [3,25,26,7,8]).…”
Section: Discussionmentioning
confidence: 99%